On the law of nations - Moynihan, Daniel P. (Cambridge Harvard University Press, 1990)
Foreign Policy. "In the annals of forgetfulness there is nothing quite to compare with the fading from the American mind of the idea of the law of nations."
Includes bibliographical references and index.
Keywords: International law--United States